Latent tuberculosis infection screening and treatment in HIV: insights from evaluation of UK practice. Issue 2 (14th October 2016) - White, Helena A; Miller, Robert F; Pozniak, Anton L; Lipman, Marc C I; Stephenson, Iain; Wiselka, Martin J; Pareek, Manish
Abstract : Latent TB infection (LTBI) screening and treatment in HIV-positive individuals in the UK is advocated by the British HIV Association (BHIVA) and National Institute for Health and Care Excellence (NICE), although each recommends differing strategies. We undertook an evaluation of UK practice, relating the responses to the local HIV/TB disease burden. 162 of 188 (86%) UK geographical areas responded; only 93/162 (57.4%) offer LTBI testing with considerable heterogeneity in practice, and no difference in HIV/TB burden between areas offering testing and those who do not. Only 33/93 (35.5%) and 6/93 (6.5%) reported full compliance with BHIVA and NICE guidance respectively. A uniform national guideline is required.